Emotion dysregulation and trait anger sequentially mediate the association between borderline personality disorder and aggression - Mancke, Falk; Herpertz, Sabine; Kleindienst, Nikolaus; Bertsch, Katja (Journal of personality disorders, 2017)
Emotion dysregulation and trait anger are seen as central aspects of aggression in borderline personality disorder (BPD); their interplay in aggression of BPD, however, remains unclear. Using a cross-sectional design, we conducted a mediation analysis in a well-characterized sample of female and male BPD patients (n = 95). We found that emotion dysregulation and trait anger sequentially mediate the association between BPD and aggression. In accordance with major theories of BPD, emotion dysregulation may thus constitute an underlying factor that gives rise to anger and in turn to aggression in BPD. These findings may help to develop mechanism-based anti-aggressive interventions for patients with BPD, which should target emotion dysregulation and anger proneness.